Chimpanzees steal less from their friends and expect them to do the same - Oded Ritov; Christoph J. Völter; Liran Samuni; Avi Benozio; Dacher Keltner; Jan M. Engelmann; Laura S. Lewis; Esther Herrmann (Evolution and Human Behavior, 2026)

Tobacco deprivation impairs metacognitive accuracy and cognitive flexibility - Alexander Soutschek; Tina Engelmann; Rebekka S. Mattes; Charlotte E. Wittekind (Psychopharmacology, 2025)
Rationale Tobacco dependence is characterized by a high relapse rate. It is thus important to obtain a better understanding of the cognitive precipitants of smoking relapses, and how these are changed under tobacco deprivation. Here, we provide evidence that tobacco deprivation impairs two cognitive processes important for successful smoking cessation: metacognition and cognitive flexibility. Methods In a pre-registered study following a within-subject design, persons who regularly smoke performed behavioral tasks measuring metacognition, motivation for mental effort, cognitive flexibility, and smoking lapses either in saturated or deprived states. Results We found that tobacco deprivation not only increased the preference for immediate rewards but also impaired metacognitive knowledge about these preferences; strikingly, these metacognitive skills were moreover related to individual lapse behavior. While there was no evidence for deprivation effects on mental effort, tobacco deprivation also impaired the ability to overcome dysfunctional cue-reward associations, indicating deficits in cognitive flexibility. Conclusions Taken together, the current findings deepen our understanding of how tobacco deprivation alters cognitive processes contributing to addictive behaviors in tobacco dependence, which may lead to improved interventions for smoking cessation.

P24-01 Impact of perinatal and subchronic dietary glyphosate exposure on gut microbiota and liver metabolism in mice - C.M.P. Martin; L. Smith; L. Evariste; F. Lasserre; A. Polizzi; V. Alquier-Bacquie; C. Dauriat; B. Engelmann; U. Rolle-Kampczyk; M. Von Bergen; B. Lamas; E. Houdeau; et al. (Toxicology Letters, 2024)

Pro- and anti-inflammatory macrophages express a sub-type specific purinergic receptor profile - J. Merz; A. Nettesheim; S. von Garlen; P. Albrecht; B. S. Saller; J. Engelmann; L. Hertle; I. Schäfer; D. Dimanski; S. König; L. Karnbrock; K. Bulatova; et al. (Purinergic Signalling, 2021)
Extracellular nucleotides act as danger signals that orchestrate inflammation by purinergic receptor activation. The expression pattern of different purinergic receptors may correlate with a pro- or anti-inflammatory phenotype. Macrophages function as pro-inflammatory M1 macrophages (M1) or anti-inflammatory M2 macrophages (M2). The present study found that murine bone marrow-derived macrophages express a unique purinergic receptor profile during in vitro polarization. As assessed by real-time polymerase chain reaction (PCR), Gαs-coupled P1 receptors A2A and A2B are upregulated in M1 and M2 compared to M0, but A2A 15 times higher in M1. The ionotropic P2 receptor P2X 5 is selectively upregulated in M1- and M2-polarized macrophages. P2X 7 is temporarily expressed in M1 macrophages. Metabotropic P2Y receptors showed a distinct expression profile in M1 and M2-polarized macrophages: Gαq coupled P2Y 1 and P2Y 6 are exclusively upregulated in M2, whereas Gαi P2Y 13 and P2Y 14 are overexpressed in M1. This consequently leads to functional differences between M1 and M2 in response to adenosine di-phosphate stimulation (ADP): In contrast to M1, M2 showed increased cytoplasmatic calcium after ADP stimulation. In the present study we show that bone marrow-derived macrophages express a unique repertoire of purinergic receptors. We show for the first time that the repertoire of purinergic receptors is highly flexible and quickly adapts upon pro- and anti-inflammatory macrophage differentiation with functional consequences to nucleotide stimulation.

Methane oxidation in anoxic lake water stimulated by nitrate and sulfate addition - Sigrid van Grinsven; Jaap S. Sinninghe Damsté; Alejandro Abdala Asbun; Julia C. Engelmann; John Harrison; Laura Villanueva (Environmental Microbiology, 2020)
Summary Methanotrophic bacteria play a key role in limiting methane emissions from lakes. It is generally assumed that methanotrophic bacteria are mostly active at the oxic‐anoxic transition zone in stratified lakes, where they use oxygen to oxidize methane. Here, we describe a methanotroph of the genera Methylobacter that is performing high‐rate (up to 72 μM day −1 ) methane oxidation in the anoxic hypolimnion of the temperate Lacamas Lake (Washington, USA), stimulated by both nitrate and sulfate addition. Oxic and anoxic incubations both showed active methane oxidation by a Methylobacter species, with anoxic rates being threefold higher. In anoxic incubations, Methylobacter cell numbers increased almost two orders of magnitude within 3 days, suggesting that this specific Methylobacter species is a facultative anaerobe with a rapid response capability. Genomic analysis revealed adaptations to oxygen‐limitation as well as pathways for mixed‐acid fermentation and H 2 production. The denitrification pathway was incomplete, lacking the genes narG/napA and nosZ , allowing only for methane oxidation coupled to nitrite‐reduction. Our data suggest that Methylobacter can be an important driver of the conversion of methane in oxygen‐limited lake systems and potentially use alternative electron acceptors or fermentation to remain active under oxygen‐depleted conditions.

Genetic makeup of Shiga toxin-producing Escherichia coli in relation to clinical symptoms and duration of shedding: a microarray analysis of isolates from Swedish children - A. Matussek; C. Jernberg; I.-M. Einemo; S. Monecke; R. Ehricht; I. Engelmann; S. Löfgren; S. Mernelius (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

A simple protocol for cryopreservation of zygotic embryos of ten accessions of coconut (Cocos nucifera L.) - O. N’Nan; M. Borges; J.-L. Konan Konan; V. Hocher; J.-L. Verdeil; J. Tregear; A. S. P. N’guetta; F. Engelmann; B. Malaurie (In Vitro Cellular & Developmental Biology - Plant, 2012)

Evolution of C4 phosphoenolpyruvate carboxylase in the genus Alternanthera: gene families and the enzymatic characteristics of the C4 isozyme and its orthologues in C3 and C3/C4 Alternantheras - U. Gowik; S. Engelmann; O. E. Bläsing; A. S. Raghavendra; P. Westhoff (Planta, 2006)

A proteomic approach to understanding the development of multidrug-resistant Candida albicans strains - H. Kusch; K. Biswas; S. Schwanfelder; S. Engelmann; P. D. Rogers; M. Hecker; J. Morschhäuser (Molecular Genetics and Genomics, 2004)

Earthworm leukocyte populations specifically harbor lysosomal enzymes that may respond to bacterial challenge - P. Engelmann; L. Molnr; L. Plinks; E. L. Cooper; P. Nmeth (Cell and Tissue Research, 2004)